2015
DOI: 10.1371/journal.pone.0119870
|View full text |Cite
|
Sign up to set email alerts
|

Heading toward the Right Direction—Solution Package for Endoscopic Submucosal Tunneling Resection in the Stomach

Abstract: BackgroundThe emerging submucosal tunneling and endoscopic resection (STER) technique provides definitive histological diagnosis as well as a therapeutic method for the gastric submucosal tumors (SMTs). We aim to present our experience and discuss key technical issues of STER.Methods45 patients with gastric SMTs arising from MP received STER. First, a mucosal incision was made 3cm proximal to the tumour, a submucosal tunnel was subsequently built from the incision to the tumor. The tumor was gradually exposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Lu et al (18) treated 18 patients with gastric fundus SMTs using STER; 19 tumors were removed, en bloc resection was achieved for all the patients and the mean tumor size was 21 mm (range, 8-50 mm). Lu et al (19) treated 45 patients with gastric SMTs using STER, 43 cases were successfully treated and 47 tumors were removed. The SMTs were all located in the cardia, the gastric fundus proximate to the cardia or the gastric antrum.…”
Section: Applications Of Stermentioning
confidence: 99%
See 4 more Smart Citations
“…Lu et al (18) treated 18 patients with gastric fundus SMTs using STER; 19 tumors were removed, en bloc resection was achieved for all the patients and the mean tumor size was 21 mm (range, 8-50 mm). Lu et al (19) treated 45 patients with gastric SMTs using STER, 43 cases were successfully treated and 47 tumors were removed. The SMTs were all located in the cardia, the gastric fundus proximate to the cardia or the gastric antrum.…”
Section: Applications Of Stermentioning
confidence: 99%
“…Although the majority of the SMTs in the MP layer are solitary, multiple studies have reported the presence of multiple SMTs (11,13,18,19,21,22). Chen et al (21) reported a patient simultaneously exhibiting esophageal and cardia SMT, and the two SMTs were successfully removed using STER with a single tunnel.…”
Section: Applications Of Stermentioning
confidence: 99%
See 3 more Smart Citations